2019
DOI: 10.21608/besps.2019.12567.1021
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Erythropoietin , Vitamin C and L-NAME in Carboplatin- Induced Hematological and Renal Dysfunctions

Abstract: Carboplatin is a neoplastic agent causing hematotoxicity, erythropoietin (EPO) resistance, increase oxidative stress and pro-inflammatory cytokines. Our study investigated the role of erythropoietin, vitamin C and L-NAME in carboplatin-induced hematological and renal dysfunctions. Seventy rats divided into seven groups; control, Carboplatin (100 mg/kg.), Carboplatin (250 mg/kg), Carboplatin (100 mg/kg.) pretreated by EPO , Carboplatin (250 mg/kg) pretreated by EPO, Carboplatin (250 mg/kg) pretreated by EPO & V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
1
0
0
1
Order By: Relevance
“…Statistical difference was significant when it was compared with Group A. These findings were comparable to other studies, [19][20][21] which showed tubular degenerative changes, including desquamation and necrosis on histological sections. It was mentioned that oxidative stress plays an important role in causing the nephrotoxicity of carboplatin by generating free radicals and reactive oxygen species.…”
Section: Discussionsupporting
confidence: 89%
“…Statistical difference was significant when it was compared with Group A. These findings were comparable to other studies, [19][20][21] which showed tubular degenerative changes, including desquamation and necrosis on histological sections. It was mentioned that oxidative stress plays an important role in causing the nephrotoxicity of carboplatin by generating free radicals and reactive oxygen species.…”
Section: Discussionsupporting
confidence: 89%
“…Hal ini karena poliuria yang disebabkan oleh kerusakan tubular yang mengarah pada dehidrasi, salah satu penyebab kenaikan BUN. 12,38,39 Karboplatin merupakan generasi kedua dari agen kemoterapi platinum yang dibuat lebih rendah efek nefrotoksisitas dan neuropati perifernya dibanding cisplatin, sehingga karboplatin menjadi alternatif pilihan lain dari cisplatin pada beberapa kanker dengan kondisi fungsi ginjal pasien yang menurun. 33,[40][41][42] Hasil penelitian oleh Chen et al (2017) menunjukkan bahwa histologi ginjal dengan pengecatan HE menggambarkan tidak adanya efek nefrotoksisitas karboplatin dan hasil qPCR yang menunjukkan bahwa karboplatin tidak memberikan efek pada kadar Organic Cation Transporter-2 (rOCT2) mRNA yang merupakan salah satu marker dari terjadinya nefrotoksisitas.…”
Section: Pembahasanunclassified